Genomic basis for pesticide degradation revealed by selection, isolation and characterisation of a library of metaldehyde-degrading strains from soil - Castro Gutiérrez, Víctor Manuel (2020)
Metaldehyde, a xenobiotic cyclic ether, is used as molluscicide of choice in agriculture and horticulture, but recently its detection in drinking water sources has become a major cause of concern. We isolated eight new metaldehyde-degrading bacterial strains from allotment and agricultural soils and identified a highly-conserved gene cluster shared amongst one gamma and five beta-proteobacteria, and absent from closely-related, non-degrading type strains. Chemical mutagenesis, and heterologous expression in E. coli, confirmed that this gene cluster is responsible for metaldehyde degradation. Other metaldehyde-degrading isolates that lack this pathway indicate that multiple degradation mechanisms have evolved. We demonstrated accelerated biodegradation of metaldehyde in multiple soils, highlighting the importance of the biological component in metaldehyde degradation in nature. We confirmed that the metaldehyde-degrading population in soil is proliferating in response to metaldehyde, but no bulk changes in the composition of the community as a whole were detected, indicating the process is governed by a few rare taxa. Here, we identified the first genetic determinants for the biological degradation of metaldehyde in soil paving the way for targeted bioremediation strategies.